Pemikiran pendekatan pembangunan di awal millenium: Penekanan pada kualitas pertumbuhan - Budiono Sri Handoko (Universitas Islam Indonesia, 2001)
Due to the economic achievement in the past 25 years, Indonesia has become one of the East Asian Miracle countries. However, this is not really true since there is an economic crisis as well as the distraction of economic fundamentals. Therefore, the new policy of economic strategy particularly by involving non economic variables can help Indonesia to solve the economi problem particularly to increase the economic growth.